VEGF-A and FGF gene therapy accelerate healing of ischemic colonic anastomoses (experimental study) - AKÇAKAYA, ADEM; Adas, Gokhan; Percem, Askin; Adas, Mine; Kemik, Ozgur; Arikan, Soykan; Ustek, Duran; Cakiris, Aris; Abaci, Neslihan; Kemik, Ahu Sarbay; Kamali, Gulcin; Karahan, Servet; et al. (My University, 2011)
Background: Reducing ischemic damage is one of the goals of surgery. The aim of this study was to apply human VEGF-A and FGF-2 DNA-mediated gene therapy in order to identify their effects in the healing of ischemic colon anastomoses and eliminating the negative effects of ischemia.